IMPLEMENTASI METODE TOPSIS (TECHNIQUE FOR ORDER PERFORMANCE BY SIMILARITY TO IDEAL SOLUTION) DALAM KEMAS ULANG KRITERIA PEMILIHAN PEMUSTAKA TERBAIK - Saputra, Andi (Journal of Documentation and Information Science, 2018)
The best user award is one of the awards given to increase visitors interest to visit the library. During this time, UPT central Library Andalas University, and most of the other libraries only used instrument of the transaction number of borrowing book as the criteria for selection. The development of library services and the utilization of information technology has demanded a review of the best selection system. In addition to the number of lending transactions, it is necessary to add the criteria of the number of visits, delay returning of borrowing and the contribution of the librarian towards the development of the library. The system involved 20 candidates based on the number of borrowing transaction and the visitation number. They were observed by the criteria delay of returning number, and scientific writing about the library. The result of assessment from each alternative which was converted into the Likert Scale in decision matrix form. The MCDM model was used for deciding the assessment result. This model is used to determine the final value of each alternative with the help of the TOPSIS method. This method is used to determine the criteria weight and calculate the value of alternative preferences. The best user is awarded by the highest references value.